HUBUNGAN ANTARA BUDAYA ORGANISASI DAN REWARD DENGAN KOMITMEN ORGANISASI - S u a r d i n S u a r d i n (Jurnal Manajemen Pendidikan, 2010)
This goals research is study to relationship of organizational culture and reward with organizational commitment at Muhammadiyah Buton's University, which has relationship each other and also together. Started from January until March 2010. Observation method that used quantitative method and corellational method. 102 person of Population, it’s taken by purporsive random sampling, determined of total sampel of population are 81 persons. This observational result founds that: (1) positive relationship available among cultural organizational with organizational commitment; (2) positive relationship available among reward with organizational; and (3) positive relationship available among cultural organizational and reward as together with organization commitment.Based this observation founds that be suggested for Rector as chairman of University expected that college have to establish policy/organization discipline and consistently, and can get created of good culture organization. Despitefully, needs repair and good reward system settlement and balanced for lecturer on Muhammadiyah Buton's University.